The Use of Gothic Fiction as a Second Language Teaching-Learning Motivational Input for Adolescents - Nido, Almudena; Díez Cobo, Rosa María (Anglo saxónica (Em linha), 2023)
It is indisputable that success in the acquisition of a second language is closely dovetailed with motivation. A direct rapport between motivation and language achievement can be traced, whereby the higher the motivation, the smoother the advances towards an effective acquisition of the target language. This process has been thoroughly explored of late in the field of Second Language Learning (SLL). Experts have rightly pinpointed that motivation dynamics greatly differ when we attend to groups of learners that tend to have a meagre and oscillating engagement with the subject matter, as it is mostly the case with adolescents. Thus, what would be at stake in this paper is the discussion of how to pair teenagers’ preferences with pertinent teaching-learning tools in the EFL (English as a Foreign Language) context. Given that the greatest challenge is to engage students’ attention and to present contents and topics that are relevant to them, it is our contention that specific literary resources as those within the Gothic narrative genre can facilitate motivation in learner-centred experience in adolescence since they resonate with key anxieties of this period. We thus side with the growing current in SLL that, over the decades, has promoted literature and extensive reading as valuable contributions to language acquisition. Our specific proposal is to incorporate the reading of Gothic fiction into the EFL secondary curriculum as a motivational spur. If teachers introduce narratives in English that have particularly appealing subject matters for our students, the teaching-learning strategies would be greatly improved.